Real wage growth in the U.S. health workforce and the narrowing of the gender pay gap - Janis Barry (BMC, 2021)
Abstract Background Healthcare has been identified as a job engine during recent recessions in the U.S. Whether the healthcare sector provides better than average pay remains a question. This study investigates if wages grew with the expanding demand for healthcare workers between 2001 and 2017. Wage growth in the (1) physicians and surgeons, (2) nurse, (3) healthcare practitioner and technical, (4) healthcare support, and (5) direct patient care jobs are examined. The gender pay gap in each occupation is investigated. Methods The American Community Survey (ACS) public use microdata sample (PUMS) for 2001, 2004, 2008, 2013, and 2017 were used to derive hourly wages for full-time, full-year workers aged 18-75. The cumulative percent change in unadjusted, median hourly wages between 2001 and 2017 was calculated for each occupation. Quantile regression estimates predicted a median hourly wage for men and women by year and job after adjusting for differences in demographics, industry, and hours worked. Results Unadjusted median wage growth was 9.92% for nurses, 5.68% for healthcare practitioners, and 37.6% for physicians between 2001 and 2017. These rates are roughly above the estimated national rate of wage growth at the 50th wage percentile. In healthcare support and direct patient care occupations, workers experienced either stagnant or negative wage growth. Women had lower occupational wages than men. Conclusion The slow or negative median wage growth in all but the physician occupation between 2004-2008 and 2008-2013 confirms that healthcare wages in the U.S. are not recession-proof, unlike healthcare employment. Generally, women's earnings grew at rates that were higher or less negative than rates for men. This trend contributed to narrowing the gender pay gap in every occupation except for nurse.